393 Keynote-826: a phase 3, randomized, double-blind, placebo-controlled study of pembrolizumab plus chemotherapy for first-line treatment of persistent, recurrent, or metastatic cervical cancer. (18th September 2019) - Tewari, K; Caceres, MV; Alexandre, J; Monk, B; Fehm, T; Colombo, N; Hasegawa, K; Dubot, C; Li, JJ; Stein, K; Keefe, S; Shapira-Frommer, R
Abstract : Objectives: For patients with recurrent/metastatic cervical cancer, incorporation of anti-angiogenesis therapy with chemotherapy yields a modest survival benefit of 3.7 months over chemotherapy alone (Tewari et al. NEJM. 2014). The rationale for checkpoint inhibition is supported by programmed death ligand-1 (PD-L1) expression in some cervical cancers (∼70%), with a higher proportion noted in squamous cell carcinoma vs adenocarcinoma. Based on the 14.3% objective response in KEYNOTE-158, the US FDA granted accelerated approval to pembrolizumab for PD-L1–positive cervical cancer for second-line therapy and beyond. Methods: KEYNOTE-826 is a phase 3, randomized, double-blind, placebo-controlled, multinational trial of chemotherapy with pembrolizumab or placebo for first-line treatment of recurrent, persistent, or metastatic cervical cancer. Patients not previously treated with chemotherapy for recurrence and not amenable to curative treatment will be randomized 1:1 to chemotherapy + pembrolizumab 200 mg or placebo every 3 weeks. The chemotherapy regimen (paclitaxel 175 mg/m 2 + cisplatin 50 mg/m 2 or carboplatin AUC 5, with or without bevacizumab 15 mg/kg) will be selected by investigators pre-randomization. Stratification factors include metastatic status at diagnosis (yes/no), bevacizumab use (yes/no), and tumor PD-L1 status (combined positive score <1, 1 to <10, or ≥10). Treatment will continue until disease progression, unacceptable toxicity, or voluntary patient withdrawal for up to 35 cycles (∼2 years). Primary endpoints are progression-free survival (PFS) per RECIST v1.1 assessed by blinded independent central review and overall survival. Secondary endpoints are objective response, duration of response, 12-month PFS, patient-reported quality of life, and safety. Enrollment is ongoing globally. ClinicalTrials.gov identifier: NCT03635567 .